Efforts of Correctional Institutions in Implementing Special Guidance for Narcotics Offenders to Prevent Recidivism at Class II A Sidoarjo Prison - Zakila Putri Nurlaily (International Journal Labs, 2025)
This research aims to analyze the efforts of the Class II A Sidoarjo Correctional Institution in implementing special guidance for narcotics-inmate users as an effort to prevent recidivism. The research uses an empirical juridical approach by examining the implementation of inmate coaching based on the provisions of Law Number 12 of 1995 concerning Corrections. Data were obtained through interviews with correctional officers, observations, and supporting literature. The results of the study show that the coaching system at the Class II A Sidoarjo Correctional Institution includes personality development, work guidance, religious coaching, and social reintegration preparation. Although coaching has generally been running in accordance with regulations, several obstacles are still found, such as overcapacity, limited facilities, and shortage of human resources. These obstacles affect the optimal implementation of coaching programs aimed at reducing the risk of narcotics inmates repeating criminal acts. To strengthen the effectiveness of coaching, improvement in infrastructure, officer professionalism, and cooperation with external stakeholders are needed.